Recreational Sports Participation Model to Enhance the Physical Fitness of Students at Fuzhou Institute of Technology - Lin, Xiaoping; Kheovichai, Kanit; Boonsom, Niwat (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: In recent years, the physical fitness of Chinese college students has been declining. There are many reasons for this situation, such as students' lack of physical exercise. How to let students make rational use of recreational time, actively participate in sports activities, develop long-term exercise habits, develop students' recreational sports participation, improve sports skills, cultivate sports interest, and gain sports experience are issues that schools should pay attention to. This study aims to develop a recreational sports participation model to improve the physical fitness of students. The main research aims are (1) to study the current situation of college students’ physical fitness and recreational sports participation at Fuzhou Institute of Technology. (2) To develop a recreational sports participation model to enhance the physical fitness of students at Fuzhou Institute of Technology. (3) To evaluate the effectiveness of the recreational sports participation model in enhancing the physical fitness of students at Fuzhou Institute of Technology. Materials and Methods: This study adoption of Research and Development(R&D) research methodology. Has the following 4 steps. Step 1 Research (R1) is to study the theories of recreational sports and the current situation of sports participation. The population is 1889 juniors in 26 majors at Fuzhou Institute of Technology, 1,133 males and 756 females. (2) Teachers of 26 majors at Fuzhou Institute of Technology. The sample are questionnaire of 344 students, interviews with 30 students, and 8 teachers. Step 2 Development (D1) is to develop the recreational sport participation model. The tools are (1) the Recreational Sports Participation Model and (2) the Physical Fitness Test Form. Step 3 Research (R2) is to implement the program of the recreational sport participation model. Stratified random sampling was used to select 104 students from 1889 juniors to participate in the 8-week experimental study. The control and experimental groups had 52 students each. There were 26 male students and 26 female students. Step 4 Development (D2) is to evaluate the recreational sport participation model. Analyze the test scores of the experimental and control groups before and after the experiment. Data analysis:(1) Experimental pre-test and post-test data were subjected to a paired samples t-test. (2) An independent samples t-test was done for the comparison of pre-test performance scores and post-test performance scores of the two groups. Results: Research (R1): The lack of organization and management in the school's sports policy. Students have enough recreational time to spend every day. However, due to the lack of awareness of physical exercise, and lack of exercise goals and plans, most of the time is spent on non-sports recreational activities. The types of projects for physical exercise are single, mainly for ball sports and running, such as basketball, badminton, and table tennis. The number of exercises and the duration of exercise are not fixed. Participating in sports helps relax the body and mind and maintain good health. Development (D1): The recreational sport participation model developed in this study uses the FITT principle. It was developed by combining the relevant dimensions of recreational sports and sports participation. That is, frequency (F), intensity (I), time (T), and type (T): behavior, motivation, limitation, and satisfaction. Research (R2): Students' post-test scores were better than pre-test scores. Students' physical fitness is enhanced, and significant changes occur. Development (D2): The results of the paired samples t-test, the post-test scores of the experimental group were higher than the pre-test scores, and there was a significant difference. The analysis of the independent samples t-test results, there is no significant difference between the pre-test scores of the experimental and control groups. The posttest scores of cardiorespiratory endurance, muscular strength and endurance, and flexibility. There is a significant difference. And there was no significant difference in the comparison of the two groups' scores for body composition. Recreational sports participation models are effective. Conclusion: College students have plenty of recreational time, but the lack of rational use of recreational time to participate in physical activity limits the discovery of physical fitness. This study analyzes the relevant theories of recreational sports and sports participation, combining students' interests, exercise habits, sports experience, satisfaction, and other factors, and is based on the relevant theories of the FITT principle. A recreational sports participation model aimed at developing college students' bodies was developed. The experimental study showed that the physical fitness post-test scores of the students in the experimental group showed a better improvement compared with the pre-test scores, and significant changes occurred. The recreational sport participation model developed in this study to develop college students' physical fitness is effective. Recreational sports participation models are effective.